F107. THE EFFECTS OF DEVELOPMENTAL STRESS AND TRAUMA ON THE DOPAMINE SYSTEM. (9th April 2019) - Bloomfield, Michael; Modaffar, Mustapha; Howes, Oliver
Abstract: Background: Exposure to developmental psychological stressors, adversity and trauma increases the risk of psychosis. Converging evidence indicates that developmental stress and trauma induce long-term changes in dopaminergic functioning which could give rise to a latent vulnerability to mental illness. I will therefore present a synthesis of the existent human and animal literature examining how developmental trauma and stress alters dopaminergic functioning in adulthood. In addition, I will present results of a study using positron emission tomography (PET) of dopamine synthesis capacity and the acute stress response in healthy adults exposed to developmental and adult psychosocial adversity. Methods: We conducted a systematic review of the animal and human literature using a combination of three superordinate concepts including 'childhood', 'trauma' and 'dopamine' terms. The PET study used [18F]-DOPA in a case-control design (n=17 per group), with one group exposed to high levels of developmental and adult psychosocial adversity and another group exposed to low levels. Acute psychological stress was induced using the Montreal Stress Task. Results: 140 studies were included in our review. Developmental stress and trauma results in long-term, complex changes in dopaminergic function across key cognitive domains including sensitization of the striatal dopaminergic response to stressors and frontal hypodopaminergia. Divergent alterations in dopaminergic function occurred depending on the timing of developmental exposure potentially representing critical periods. Developmental stress exposure potentiates aspects of dopaminergic processing including amplifying threat-related signaling in the ventral (limbic) striatum. This may occur alongside dopaminergic blunting in the amygdala resulting in deficits in fear extinction, impairing the ability to distinguish safe from unsafe environments. In our PET experiment, within people without psychosis long-term psychosocial adversity was associated with reduced baseline dopamine synthesis capacity and de-coupling between striatal dopamine and the acute stress response. Discussion: Developmental trauma exposure is likely to be inducing latent vulnerability to psychosis by producing lasting changes in reward, threat and executive processing. Further studies are needed to investigate the precise mechanisms underlying how trauma-induced changes in dopaminergic function induce vulnerability to psychosis and, in parallel, how dopaminergic processes may confer resilience.